PENGARUH SENAM NIFAS TERHADAP PROSES INVOLUSI UTERI PADA IBU POSTPARTUM - Hidayah, Ardiyanti; Dian Anggraini, Rista (LPPM STIKES HUSADA JOMBANG, 2023)
Postpartum hemorrhagic is caused by improper uterine involution, therefore early ambulation with postpartum exercise is needed. Postpartum gymnastics is one way of early mobilization that is highly mandated for post partum mothers so that the involution process runs smoothly. The aim of the study was to determine the effect of postpartum exercise on uterine involution in post partum at the Prima Wiyata Husada clinic, Mancar Village, Peterongan District, Jombang Regency in 2020. The research method was pre-experimental with 30 post normal respondents. mothers giving birth at the Prima Wiyata Husada clinic in Mancar Village, Peterongan District, Jombang Regency consisting of 15 mothers who did postpartum exercises (experimental respondent group). And 15 mothers who did not do purperal exercises (control group). The data collection used observation while the formula used the dependent t-test, the results of research on the speed of uterine involution in mothers who did postpartum exercise were mostly in the fast category as many as 8 people (53.3%), the rest were in the normal category as many as 5 people (33.3%) %) %), whereas in the slow category it does not come out (0.00%). The uterine involution rate in postpartum women who did not do postpartum exercise was mostly in the slow category as many as 9 people (60.6%), the rest in the normal category were 4 people (26.6%), while in the fast category there were 2 people (13, 6%) 3%). Can resolve differences in changes in uterine involution between the intervention group and the control group